Prevalence of Root Canal Morphology of Mandibular Molar in Western Nepalese Population: A Cross-sectional Study - Tripathi, Rupam; Nepal, Manisha; Gautam, Vanita; Sah, Rinku; Shrestha, Kriti; Thapa, Sujan (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: A main variant in the mandibular molars is the presence of radix entomolaris (RE) and radix paramolaris (RP) in the mandibular first molars and fused roots in 2nd mandibular molar. Hence, the present prospective study intends to evaluate the prevalence of radix entomolaris, radix paramolaris and molars with fused roots in a local population of Western Nepal. MATERIAL AND METHODS: This is prospective cross-sectional study. The total of 336 patient's mandibular first and second permanent molars having radiological and clinical evidence of pulpal pathology were included in this study. The criteria for the identification of an extra root were justified by crossing of the translucent lines defining the pulp space and periodontal ligaments in the mandibular first molars, and for the mandibular second molars, the outline of the periodontal ligament was followed to see the presence of the fused roots. RESULTS: Thirty nine patients (24 females and 15 males) showed a supernumerary distolingual root (RE) in mandibular first molars and 42 patients (18 females and 24 males) showed mesiolingual root (RP). The prevalence of patients with radix entomolaris was 11.6% (39 of 336), 13.6% for females (24 of 176) and 9.3 % for males (15 of 160). The prevalence of radix paramolaris was 12.5%(42 of 336), 10.5%(18 of 176) for females and 15% (24 of 160) for males. 54 patients (27 females and 27 males) showed C-shaped canals in mandibular molars. The prevalence of C-shaped mandibular molars was 30% for females (27 of 90) and 34.6% (27 of 78) for males. There was statistically no significant difference in the prevalence of entomolaris, paramolaris and C-shaped canals among male and female population. CONCLUSION: Failure to diagnose radix entomolaris, paramolaris and fused root may lead to missed canal and incomplete debridement of canal resulting in compromised treatment outcome. The successful endodontic therapy employed all the roots and canals to be located, cleaned, shaped and obturated.